Enhanced Contextual Fear Memory and Elevated Astroglial Glutamate Synthase Activity in Hippocampal CA1 BChE shRNA Knockdown Mice - Chen, Si; Lin, Zhengdong; Tan, Kai-Leng; Chen, Risheng; Su, Wenfang; Zhao, Haishan; Tan, Qiwen; Tan, Wen (Frontiers in Psychiatry, 2020)
Butyrylcholinesterase (BChE) efficiently hydrolyzes acetylcholine (ACh) at high concentrations when acetylcholinesterase (AChE) is substrate-inhibited. Recent studies have shown that BChE also has a function that is independent of ACh, but it has not been fully explored. Low BChE expression is accompanied with higher stress-induced aggression and ghrelin levels in stress models, and BChE knockout mice exhibit cognitive and memory impairments. However, the role of BChE in posttraumatic stress disorder (PTSD) remains unclear. In the present study, we investigated the role of BChE in contextual fear memory and its regulatory effect on the expression of factors related to the glutamate (Glu)-glutamine (Gln) cycle via knockdown studies. We used AAVs and lentiviruses to knockdown BChE expression in the mouse hippocampal CA1 region and C8D1A astrocytes. Our behavioral data from those mice injected with AAV-shBChE in the hippocampal CA1 region showed strengthened fear memory and increased dendritic spine density. Elevated Glu levels and glutamine synthetase (GS) enzyme activity were detected in contextual fear conditioned-BChE knockdown animals and astrocytes. We observed that an AAV-shBChE induced lowering of BChE expression in the hippocampus CA1 enhanced contextual fear memory expression and promoted the astrocytic Glu-Gln cycle but did not elevate ACh-hydrolyzing activity. This study provides new insight into the regulatory role of BChE in cognition and suggests potential target for stress-related psychiatric disorder such as posttraumatic stress disorder (PTSD) where patients experience fear after exposure to severe life-threatening traumatic events.